2008
DOI: 10.2174/1874364100802010137
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Findings Among Nigerian Paediatric Glaucoma Suspects During A School Eye Health Survey

Abstract: Objective:To report clinical findings suspicious of glaucoma among primary school children in Ilorin, Nigeria.Methods:A cross sectional survey of ocular health among 1,393 school children carried out between July 2005 and January 2006. Criteria for suspecting glaucoma included a cup disc ratio (CD) of > 0.5, a CD asymmetry between the fellow eyes of > 0.2, and/or intraocular pressure (IOP) > 21mmHg by applanation tonometry.Results:Eleven (6 boys and 5 girls) of 1,393 pupils (0.8%), aged between 7 and 13 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…[18] Glaucoma suspects constituted 3.7%. This was relatively high compared to the findings in south western Nigeria by Ayanniyi, [19] (0.8%) six years ago. The prevalence may have risen over the years or originally high in this part of the country.…”
Section: Discussioncontrasting
confidence: 60%
“…[18] Glaucoma suspects constituted 3.7%. This was relatively high compared to the findings in south western Nigeria by Ayanniyi, [19] (0.8%) six years ago. The prevalence may have risen over the years or originally high in this part of the country.…”
Section: Discussioncontrasting
confidence: 60%
“…Medical management of glaucoma in children remains a powerful tool. A Nigerian study screened for glaucoma among 1,393 dark-skinned primary school children between 7 and 13 years of age; they found that eleven (0.8%) were glaucoma suspects 25. Suspicious optic discs and elevated IOP were the first and second most common features.…”
Section: Discussionmentioning
confidence: 99%
“…A Nigerian study screened for glaucoma among 1,393 dark-skinned primary school children between 7 and 13 years of age; they found that eleven (0.8%) were glaucoma suspects. 25 Suspicious optic discs and elevated IOP were the first and second most common features. Another Nigerian study found that ten of 327 schoolchildren (3.2%) were glaucoma suspects.…”
Section: Discussionmentioning
confidence: 99%
“…Also, to provide a better view of the retina's periphery, binocular indirect ophthalmoscopy was done for each subject using a handheld + 20 DS lens (Appasamy, India). The optic disc, retina, retinal blood vessels and macula were viewed in each eye and posterior segment lesions were said to be present when one or more of the following ocular lesions were seen; Retinal vascular tortuosity, Salmon patch, Black sunburst, Macular hyperpigmentation, Iridescent bodies, Optic atrophy, Glaucomatous optic disc 21,[25][26][27][28] :…”
Section: Methodsmentioning
confidence: 99%